2020
DOI: 10.1007/s12253-020-00801-7
|View full text |Cite
|
Sign up to set email alerts
|

Significance of HPV16 Viral Load Testing in Anal Cancer

Abstract: Human papilloma virus (HPV) is highly frequent among patients with anal squamous cell carcinoma, but the viral load (VL) differs between patients. This study aimed to compare the rate of HPV positivity, HPV16VL, p16 INK4A and p53 expression between treatment naive and recurrent anal cancer patients. HPV was genotyped via AmpliSens® HPV HCR-genotype-titre-FRT kit. HPV16 VL was determined via quantitative polymerase chain reaction-based in-house test. p16 INK4A and p53 expression was tested via immunohistochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
5
0
2
Order By: Relevance
“…Complimentary studies have investigated the implications of HPV viral load in and around the anal canal, 28‐32 however, the majority of the available publications have looked into HPV load in people living with HIV. Other studies have assessed VL in anal cancer 31,32 and found a median of 7.40 and 134 copies/cell. However, to our knowledge only one investigation has explored the association between HPV load, local control of cancer and overall survival 31 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complimentary studies have investigated the implications of HPV viral load in and around the anal canal, 28‐32 however, the majority of the available publications have looked into HPV load in people living with HIV. Other studies have assessed VL in anal cancer 31,32 and found a median of 7.40 and 134 copies/cell. However, to our knowledge only one investigation has explored the association between HPV load, local control of cancer and overall survival 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Complimentary studies have investigated the implications of HPV viral load in and around the anal canal, 28 , 29 , 30 , 31 , 32 however, the majority of the available publications have looked into HPV load in people living with HIV. Other studies have assessed VL in anal cancer 31 , 32 and found a median of 7.40 and 134 copies/cell. However, to our knowledge only one investigation has explored the association between HPV load, local control of cancer and overall survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В нашем исследовании при анальном раке и РШМ ВПЧ ВКР выявлен во всех образцах, что согласуется с данными, опубликованными ранее зарубежными авторами об этиологическом сходстве возникновения РШМ и анального рака [3,12,21]. Средняя величина вирусной нагрузки (5,7-5,8 lg ДНК ВПЧ/10 5 клеток) при III-IV стадиях рака анального канала, РШМ и HSIL подтверждает гипотезу, что большое число копий генома ВПЧ увеличивает вероятность интеграции вирусной ДНК в геном хозяина, что может играть роль в канцерогенезе инвазивного рака и прогрессировании заболевания [19,20].…”
Section: Discussionunclassified
“…Уровень ВПЧ-позитивности выше среди женщин. При исследовании вирусной нагрузки ВПЧ 16 выявлено, что она была выше в группе больных, ранее не получавших лечения [19]. Установлено, что ВПЧ-позитивность была связана с лучшей выживаемостью и ответом на химио лучевую терапию (подобно плоскоклеточному раку головы и шеи), а низкая вирусная нагрузка была прогностическим фактором более низкой общей выживаемости [1,17].…”
Section: Introductionunclassified